UTILIZATION OF MAGGOT BLACK SOLDIER FLY (Hermetia illucens) AS A SUBSTITUTE OF COMMERCIAL RATIONS FOR DIGESTIVE ORGAN OF BROILER - A.R., Pramesti; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of using Maggot Black Soldier Fly (Hermetia illucens) as a substitute for commercial rations on the weight of broiler digestive organs. The design used was a completely randomized design consisting of four treatments and four replications, each replication consisting of four broilers. The treatment consisted of P0 (rations without replacement with maggot), P1 (5% commercial ration was replaced with 5% maggot), P2 (10% commercial ration was replaced with 10% maggot), P3 (15% commercial ration was replaced with 15 % maggot). The variables observed were the length of the small intestine, the weight percentage of the small intestine, bile, liver, pancreas, proventriculus, and ventricles. The results of this study showed that the length of the small intestine in the P1, P2, and P3 treatments was significantly different (P<0,05) higher than the P0 treatment, and the percentage of small intestine weight in the P1 and P3 treatments was significantly different (P<0,05) more higher than the P0 treatment, while the P2 treatment was not significantly different (P>0,05) higher than the P0 treatment, then the weight percentage of bile, liver, pancreas, proventriculus, and ventricles produced no significant difference (P>0,05) compared to the P0 treatment P0. The results of this study can be concluded that the utilization of 5%, 10%, and 15% maggot in commercial rations can increase the length of the small intestine and the percentage of small intestine weight, but gives the same results for the weight percentage of bile, liver, pancreas, proventriculus, and ventricles.